KERAGAMAN GENETIK CENDANA PADA TEGAKAN PENGHASIL BENIH DAN TEGAKAN REHABILITASI DI NUSA TENGGARA TIMUR BERDASARKAN PENANDA ISOZIM - Rini Purwiastuti; Sapto Indrioko; Eny Faridah (Jurnal Pemuliaan Tanaman Hutan, 2016)
This study aimed to determine the genetic diversity of sandalwood on seed production stand and rehabilitation stand in East Nusa Tenggara using isozyme genetic marker. The study was conducted using samples collected from three stands, i.e. Seed Production Area (APB) representing seed production stand, KHDTK rehabilitation stand and CSR rehabilitation stand representing rehabilitation stands. Samples of sandalwood juvenile leaves are taken randomly from each location. Sample materials taken were juvenile leaves collected randomly from each stand. There were 57 samples taken from APB, while each 25 samples were collected from rehabilitation stands of KHDTK and CSR. Isozymes analyses were carried out in the laboratory using three kinds of enzyme systems i.e Esterase (EST), Diaphorase (DIA) and Shikimate Dehydrogenase (SHD). The results showed that for genetic diversity within stands, the mean of polymorphic loci was 88.89%, with a mean number of alleles per locus 2.1667 and a mean of effective alleles 1.2103. The expected heterozygosity within stands (HS) was 0.1558, with the observed heterozygosity (HO) of 0.1402, while the mean index of fixation (FIS) was 0.1118. On genetic diversity among stands, DST, and GST values were 0.0090 and 0.0545 respectively, while total expected heterozygosity of the three stands (HT) was 0.1648. To anticipate sandalwood genetic diversity decline, it is essential to identify and record the remaining sandalwood populations, then conserve rare alleles either through in-situ or ex-situ conservation programs.